Christian Caritas in Christian Pedagogy - Aftyka, Leszek (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article highlights the leading ideas of Christian pedagogy, which are the upbringing of children and youth of spiritual and moral values. The author stresses that Christian pedagogy serves the effective tool for the formation of the spirituality of the younger generation, the formation of philosophical representations and beliefs, etiquette, spiritual traditions and values of people in the universally accepted commandments of God. Considerable attention is paid to the formation of high morality of the younger generation, etiquette, love of people, religiousness, etc. In the Christian religion the highest value compared to all other virtues is „love”. The Christian love is rooted primarily in the commandment of love for God and man, that is why genuine charity comes from the heart full of love. This article presents the teaching of Christ for mercy to others and its practical application in the first Christian Communities. The author described the economic organization and charitable initiatives in the communities of early Christians